Modifiable Factors Associated With Poststroke Physical Activity at Discharge From Rehabilitation: Prospective Cohort Study. Issue 5 (29th January 2020) - Thilarajah, Shamala; Bower, Kelly J; Pua, Yong-Hao; Tan, Dawn; Williams, Gavin; Larik, Ashfaq; Bok, Chek-Wai; Koh, Gerald; Clark, Ross A
Abstract: Background: People with stroke are not meeting recommended levels of physical activity. The modifiable factors associated with poststroke physical activity levels need to be identified to develop targeted interventions. Objective: The objective of this study was to investigate the factors at discharge from inpatient rehabilitation that are associated with physical activity levels at 3 months following discharge. Design: This was a prospective cohort study. Methods: Sixty-four people with stroke completed baseline assessments at discharge from inpatient rehabilitation and 55 completed the follow-up 3 months later. The candidate factors (ie, gait speed, balance, strength, cognition, mood, and motivation) were measured at discharge. The primary outcome measure at follow-up was walking-related activity (measured by wrist-worn accelerometer). Secondary outcome measures were physical activity participation (Activity Card Sort) and intensity of physical activity (International Physical Activity Questionnaire–Short 7 days). Adjusted separate multivariable linear regression models or proportional odds regression models were used to evaluate the associations between candidate factors and physical activity. Results: Gait speed and balance were associated with all aspects of physical activity. Higher level of intrinsic motivation was also associated with higher physical activity participation. Anxiety demonstrated a significant nonlinear relationship with physical activity participation. Limitations: Inclusion of fatigue and individual muscle strength could have provided further insights into associations with steps per day. Conclusion: The results demonstrated that better physical function at discharge from inpatient rehabilitation was associated with future increased levels of physical activity. Additionally, higher levels of motivation impacted on increased physical activity participation. The influence of anxiety on physical activity participation requires further exploration. Mixed-method study designs can be utilized to further understand the factors associated with poststroke physical activity.